A novel approach for agricultural carbon emission reduction by integrating fermatean neutrosophic set with WINGS and AHP-EWM - Kecheng Zhang; Zhicheng Chen; Yawen Wang (Scientific Reports)
Abstract Agriculture is a major contributor to global greenhouse gas emissions, highlighting the urgent need for effective carbon reduction strategies. This study presents an innovative integrated model that employs Fermatean Neutrosophic Set in conjunction with the Weighted Influence Nonlinear Gauge System and the Analytic Hierarchy Process combined with the Entropy Weight Method to assess key factors influencing agricultural carbon reduction. Our study delineates the hierarchical importance of factors influencing carbon emissions, with carbon emission reduction policy (τ4) emerging as the paramount factor, attributed a value of 0.220. The factor prioritization is ordered as τ4 > τ8 > τ3 > τ2 > τ6 > τ9 > τ1 > τ5 > τ7. Concurrently, the causality ranking, derived from the $$\:S_{\mathcal{H}-\mathcal{L}}$$ values, positions agricultural technology adoption (τ6) as the most influential factor, with a value of 0.7737, and is followed by the sequence τ6 > τ9 > τ8 > τ1 > τ5 > τ2 > 0 > τ3 > τ4 > τ7.The findings emphasize the pivotal role of sustainable agricultural management, carbon emission reduction policy, and agricultural technology adoption in mitigating emissions, and based on this, suggest some policy insights that can be used by policymakers and regulators. The proposed model serves as a robust decision-making tool for policymakers and provides a theoretical framework for developing effective agricultural carbon reduction strategies. This research advances the field by offering a novel theoretical model for complex decision-making under uncertainty, deepening the understanding of agricultural carbon reduction dynamics, and providing actionable insights for sustainable development.